Toothpick ingestion causing rectum perforation - Emir Çapkınoğlu; Oğuzhan Özsay; Atilla Örsel; Serkan Karaisli (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Çapkınoğlu E, Özsay O, Örsel A, Karaisli S. Toothpick ingestion causing rectum perforation. Turk J Gastroenterol 2017; 28: 540-1.